Water leakage detection using remote sensing, field spectroscopy and GIS in semiarid areas of Cyprus - Agapiou, Athos; Alexakis, Dimitrios; Themistocleous, Kyriacos; Hadjimitsis, Diofantos G. (My University, 2016)
Water pipelines need to be systematically monitored in order to minimize losses from possible leakages. In this paper, remote sensing techniques have been exploited in semiarid areas of Cyprus. In addition, ground spectroradiometer has been used to define the leakage’s threshold values. The data were analysed in a GIS environment. Two known leakage problems have been examined. In the first case study, a high resolution QuickBird image was used for the detection of the exact point of leakage. In the second case study a multi-temporal analysis was performed using SPOT images. This methodology was able to record 10 possible leakage points along the pipeline. Throughout the 25 km length of the pipeline, the in-situ observations were minimized to only 0.4%. In both studies the Normalised Difference Vegetation Index (NDVI) was applied. The final outcomes highlight the contribution of remote sensing to the early detection of leakages especially in difficult and near inaccessible areas.
Keywords: Water leaks; Remote sensing; Water management; Water losses; NDVI; QuickBird; SPOT 5